Complex Evaluation of Surfactant Protein A and D as Biomarkers for the Severity of COPD - Lv MY; Qiang LX; Wang BC; Zhang YP; Li ZH; Li XS; Jin LL; Jin SD (International Journal of COPD, 2022)
Mei-Yu Lv, Li-Xia Qiang, Bao-Cai Wang, Yue-Peng Zhang, Zhi-Heng Li, Xiang-Shun Li, Ling-Ling Jin, Shou-De Jin Department of Respiratory Medicine, The Fourth Affiliated Hospital of Harbin Medical University, Harbin, 150001, People’s Republic of ChinaCorrespondence: Shou-De Jin, Department of Respiratory Medicine, The Fourth Affiliated Hospital of Harbin Medical University, No. 37 Yiyuan Street, Nangang District, Harbin, 150001, People’s Republic of China, Tel/Fax +86 0451-85939123, Email jinshoude@163.comPurpose: Pulmonary surfactant proteins A (SP-A) and D (SP-D) are lectins, involved in host defense and regulation of pulmonary inflammatory response. However, studies on the assessment of COPD progress are limited.Patients and Methods: Pulmonary surfactant proteins were obtained from the COPD mouse model induced by cigarette and lipopolysaccharide, and the specimens of peripheral blood and bronchoalveolar lavage (BALF) in COPD populations. H&E staining and RT-PCR were performed to demonstrate the successfully established of the mouse model. The expression of SP-A and SP-D in mice was detected by Western Blot and immunohistochemistry, while the proteins in human samples were measured by ELISA. Pulmonary function test, inflammatory factors (CRP, WBC, NLR, PCT, EOS, PLT), dyspnea index score (mMRC and CAT), length of hospital stay, incidence of complications and ventilator use were collected to assess airway remodeling and progression of COPD.Results: COPD model mice with emphysema and airway wall thickening were more prone to have decreased SP-A, SP-D and increased TNF-α, TGF-β, and NF-kb in lung tissue. In humans, SP-A and SP-D decreased in BALF, but increased in serum. The serum SP-A and SP-D were negatively correlated with FVC, FEV1, FEV1/FVC, and positively correlated with CRP, WBC, NLR, mMRC and CAT scores (P < 0.05, respectively). The lower the SP-A and SP-D in BALF, the worse the lung function and the increased probability of complications and ventilator use. Moreover, the same trend emerged in COPD patients grouped according to GOLD severity grade (Gold 1– 2 group vs Gold 3– 4 group). The worse the patient’s condition, the more pronounced the change.Conclusion: This study suggests that SP-A and SP-D may be related to the progression and prognostic evaluation of COPD in terms of airway remodeling, inflammatory response and clinical symptoms, and emphasizes the necessity of future studies of surfactant protein markers in COPD.Keywords: COPD, pulmonary surfactant protein A and D, airway remodeling